BIOLOGÍA DE LAS CÉLULAS DENDRÍTICAS HUMANAS - Cuéllar Ávila, Adriana; Grupo de Inmunobiología y Biología Celular Departamento de Microbiología Facultad de Ciencias Pontificia Universidad Javeriana, Bogotá (2004)
Antigen presenting cells are capable of capturing and processing antigenic peptides to be presented to T lymphocytes in the context of the Major Histocompatibility Complex. These peptides derived from self or no self proteins could be recognized  by the T Cell Receptor expressed on the surface of T lymphocytes. However, this presentation is not enough to activate peptide specific T lymphocytes. Dendritic cells are potent antigen presenting cells and  also have the capability to generate a second signal to stimulate T cell response. Currently, dendritic cells seem to play a central role in the  development of autoimmune diseases and also in the immune response  to microbial and tumoral antigens. The active study of their function and the possibility to purify dendritic cells form peripheral blood and even differentiate them in vitro from blood precursors will allow future and new  immune therapies for several diseases.